Developing BoardWise : A Digital Board Game for Enhancing Elementary Science Education - Ali, Fathan Faqih; Sari, Prima Mutia (Universitas Pendidikan Mandalika, 2025)
This study aims to develop and determine the feasibility of a digital board game,